Understanding trends in osteoporosis drug prescribing: implications for reducing futile biomedical research - Guillemot, Jonathan R.; Abraham, John W.; Tinker, Anthea (Frontiers in Medicine, 2025)
IntroductionOsteoporosis is a significant geriatric condition, considering its impact on fracture-related morbidity and mortality, particularly among older women. The interplay of clinical evidence, diagnostic tools availability, and broader societal attitudes toward aging and treatment efficacy affect medical attitude and prescribing behaviors. Using the example of osteoporosis in France and England, the study aims to unravel the intricacies of medical decision-making in geriatric care, offering insights into the evolving landscape of healthcare policy and practice, which in turn can help reduce futile biomedical research.MethodsWe employed documentary analysis and semi-structured interviews. Documentary analysis involved examining public policy documents related to osteoporosis management in England and France to identify trends in regulatory policies influencing prescribing practices. Semi-structured interviews with physicians explored prescriber decision-making processes, treatment initiation, and compliance management, providing insights into clinical practice complexities.ResultsThe policy analysis uncovered 157 documents between 2015 and 2016, updated in 2018, revealing distinct policy clusters and outliers shaping osteoporosis management in England and France. Therapeutic indications generally mirrored marketing authorizations. Reimbursable therapeutic indications in France showed fluctuating availability, reflecting changes in policy priorities and patient demographics. Clinical guidelines evolved to encompass diverse osteoporosis types and treatment options, guided by evidence-based recommendations and healthcare system considerations. Trust dynamics between physicians, pharmaceutical companies, and health authorities influenced prescribing trends, with variations in reliance on standardized protocols and collaborative decision-making observed between England and France.DiscussionUnderstanding trends in osteoporosis drug prescribing is crucial for optimizing healthcare policy and practice. Our study highlights the complex factors influencing prescribing patterns in England and France, emphasizing the role of trust in shaping physician behaviors. By addressing barriers to treatment uptake and enhancing patient outcomes, targeted interventions can be developed to reduce futile biomedical research and improve healthcare resource allocation.